The Impact of Prison on Marital Rights - A comparative Study - - Al-Namash, AbdulRahman Mohammed Youssef; AbdulRaheem, Ahmed Hammad Abdullah; Al-Jazuli, AbdulRahman Adam Othman (Arab Journal for Sciences and Research Publishing, 2017)
This study dealt with the impact of prison on marital rights in Islamic sharia and human laws. The study aimed at focusing on this rights and to what extent they are implemented in prisons, in addition to the effectiveness of the legislations organising them in Sudan. The paper also tackled the understanding of prison, its kinds and its legality in addition to the marital rights for the benefit of both of the married or for each one on the other independently. So the study arrived at many results, here are the most important of them: 1- Dealers of person have the right to practise their marital rights in prison, so preventing them from this right is supposed to be a crime. 2-Reformation of the guilty was the focus of the Sudanese penalty establishments, which is quite visible in inventing modern means for prisoners to practise their marital rights which makes them positive members in society. 3- The answering of practising marital rights question, lightens the psychological tensions of the prisoner, simultaneously keeps his wife away from adultery. 4- Practising marital rights in prison duration is supposed to be a legislative end, as support to the doctrine of self keeping. 5- Regulations organizing the marital rights of prisoners in Sudanese penalty establishments are inadequate.